Restructuring and functional heads - Cinque, Guglielmo (Oxford University Press, 2006)
Collects the articles of Guglielmo Cinque of the University of Venice. This book is divided into two sections, the first on restructuring, a central topic in Romance syntax and with connections to other language groups as well. The second part focuses on the consequences of treating clausal functional heads as members of a universal hierarchy.
Keywords: Grammar, Comparative and general -- Syntax.; Romance languages -- Syntax.; Syntaxe.; Langues romanes -- Syntaxe.; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Syntax.; Grammar, Comparative and general -- Syntax; Romance languages -- Syntax; Wortstellung; Bewegung -- Linguistik; Minimalist program -- Linguistik; Funktionale Kategorie; Hoofd (taalkunde); Werkwoorden.; Grammaticale functie.; Syntaxis.; Sintaxe.; Gramática comparada.; Lingüística indo-européia.